Case Report: Metagenomics Next-Generation Sequencing for Diagnosing Cerebral Infarction and Infection Caused by Hematogenous Disseminated Mucormycosis in a Patient With Acute Lymphoblastic Leukemia - Wen, Bingbing; Cai, Lisheng; Cai, Yun; Du, Xin (Frontiers in Medicine, 2021)
Disseminated mucormycosis, a serious complication, is associated with high mortality in patients with acute leukemia after chemotherapy. Blood cultures are always negative because of recurrent empirical antifungal treatments. The identification of pathogens is important for diagnosis and therapy. In this case report, we diagnosed culture-negative disseminated mucormycosis with Rhizomucor miehei infection leading to cerebral infarction in a patient with leukemia using metagenomics next-generation sequencing (mNGS) form peripheral blood, cerebral spinal fluid, and bronchoalveolar lavage fluid. mNGS technology can be applied to precisely diagnose culture-negative disseminated mucormycosis.